Meningkatkan Mutu Pendidikan Islam di Arah Era Pembaharuan - Rahmawati Rahmawati; Iin Purnamasari; Dwi Noviani (STIKes Ibnu Sina Ajibarang, 2023)
Islamic education has experienced a significant transformation along with the times. In this era of renewal, improving the quality of Islamic education is a necessity to ensure future generations are qualified and able to face global challenges. This article explains various innovations and challenges related to efforts to improve the quality of Islamic education. Through a holistic approach, Islamic education can integrate traditional values ​​with technological developments and contemporary needs, creating an educational system that is relevant and competitive.